A randomized, double-blind study to compare the efficacy and safety of two doses of mometasone furoate delivered via Breezhaler® or Twisthaler® in patients with asthma. (June 2020) - Buhl, Roland; Tanase, Ana-Maria; Hosoe, Motoi; Cao, Weihua; Demin, Ivan; Bartels, Christian; Jauernig, Jürgen; Ziegler, Dominik; Patalano, Francesco; Hederer, Bettina; Kanniess, Frank; Tillmann, Hanns-Christian
Abstract: Introduction: Mometasone furoate (MF) is the inhaled corticosteroid (ICS) component in the long-acting β2 -agonist (LABA)/ICS fixed-dose combination of indacaterol/MF, delivered via Breezhaler®, in development for asthma. MF at low (80 μg) and high (320 μg) doses delivered via Breezhaler® is expected to be comparable to MF at low (200 μg) and high (800 μg) doses respectively, delivered via Twisthaler®. Methods: This was a randomized, double-blind, double-dummy, four-week, parallel-group study of 739 adolescents and adults with persistent asthma. Eligible patients were receiving ICS treatment up to the maximum dose per day on a stable regimen for at least four weeks before screening. The study population was enriched for patients who were responsive to ICS therapy. The primary objective of the present study was to show non-inferiority of these doses, i.e. the low (80 μg) and high (320 μg) doses of MF delivered via Breezhaler® once daily, compared with the corresponding low (200 μg) and high (800 μg) doses of MF delivered via Twisthaler® once daily. The primary endpoint was 24 h post-dose trough forced expiratory volume in 1 s (FEV1 ), after four weeks of treatment in patients with asthma. A secondary objective was to evaluate the efficacy of MF 80 μg and 320 μg delivered via Breezhaler®, and MF 200 μg and 800 μg delivered via Twisthaler® in terms of Asthma Control Questionnaire-5 (ACQ-5) after one, two, three and four weeks of treatment. Results: The LS mean difference in trough FEV1 after four weeks of treatment between MF low dose 80 μg (Breezhaler®) and MF low dose 200 μg (Twisthaler®) was 27 mL (95% CI –34, 89); for MF high dose 320 μg (Breezhaler®) and MF high dose 800 μg (Twisthaler®) the difference was 0 mL (95% CI –60, 61). These differences were neither clinically nor statistically significant. All treatment arms provided similar clinically relevant improvements in ACQ-5 after four weeks of treatment compared with baseline. Both treatments showed a similar safety profile with a low incidence of adverse events. Conclusion: The similarities in effects on lung function and ACQ after four weeks of treatment demonstrate the comparability of MF at low (80 μg) and high (320 μg) doses delivered with Breezhaler® with MF at low (200 μg) and high (800 μg) doses delivered with Twisthaler®, respectively. The study formally demonstrated that MF, delivered via Breezhaler®, is non-inferior to MF, delivered via Twisthaler® at corresponding ICS doses.